Efforts to increase student participation, achievement motivation, and learning outcomes through the active learning model type everyone is a teacher here in the subject of sociology class XI of SMA Negeri 2 Menyuke - Rodi, Rodi; Sulistyarini, Sulistyarini; Fatmawati, Fatmawati (Universitas Tanjungpura, 2024)
This research was conducted in an effort to improve student participation, achievement motivation, and learning outcomes through the Active Learning Model Type Everyone is A teacher Here in the subject of sociology for grade XI students at SMA Negeri 2 Menyuke. This research is generally motivated by the fact that the learning outcomes of students in this subject at SMA Negeri 2 Menyuke are still low. Many efforts have been made, but they have not provided maximum results. The use of the everyone is A teacher here (ETH) learning model in this research is an innovative effort in sociology learning at SMA Negeri 2 Menyuke. The method used is Classroom Action Research, with the research subjects being grade XI IPS 1 students at SMA Negeri 2 Menyuke. In addition to observation to observe the implementation of the action and student participation in learning, the instruments used in this research are also questionnaires to collect data on achievement motivation and learning outcome tests to measure the success of learning using this method. There are two cycles used in this research, and it is concluded after the second cycle is implemented. The results of the research show that the use of everyone is a teacher here (ETH) can improve student participation, achievement motivation, and learning outcomes in sociology for grade XI IPS 1 students at SMA Negeri 2 Menyuke. The research results recommend that sociology teachers use this method by varying it with various relevant media.